SISTEM PENGONTROLAN DAN MONITORING LEVEL TEGANGAN PLC SECARA WIRELESS BERBASIS EMBEDDED LINUX. - Muhammad Agil Haikal; Rouhillah; Effendi (J-Innovation, 2015)
Programmable Logic Controller (PLC) is not only serves as a smart relay or just on and off the system but also provided an analog input so that the PLC can changes in input voltage levels. PLC also has a serial communication between PLC coupling with other devices. Level analog voltage input has a voltage rating of 0-10 Volt will be converted by the ADC (analog digital converter) to the PLC, and the subsequent response of the ADC program created in the PLC will affect the results output. This reseach was made for monitoring levels of 0-10 Volt input voltage that come from the PLC. ADC control is made will be downloaded to the PLC. PLC will be communicated with the Raspberry Pi which is installed embedded linux-based operating system via Modbus communications, thus controlling which previously via PLC can be taken over by the Raspberry Pi. This research also made for monitoring the working of the system, because the Raspberry Pi was be equipped by wireless that will be used for communication to a PC (personal computer) without using cables. the results of this research is a wireless PC can monitor changes 0-10 Volt analog voltage, the output response on the PLC and PLC output can be controlled in accordance with the desired system